P463Fractional flow reserve guided percutaneous coronary intervention; does long term data support its efficacy (a real world single centre experience in consecutive patients). (15th July 2014) - Khan, A; Low, C; Almarzouqi, J; Foley, D
Abstract: Purpose: Fractional Flow Reserve (FFR) is a guide wire-based procedure that can accurately measure flow through a specific part of the coronary artery by placing a pressure guidewire across the lesion and pharmacologically induced hyperaemia.The aim of our study was to determine the long term clinical cardiovascular outcome, of patients who underwent FFR guided percutaneous coronary intervention. Methods: Data of 132 consecutive patients (mean age ± 1 SD, 69 ± 8.4 years) who underwent FFR between January 2004 and Dec 2009. Data was obtained from the cardiac catheterization lab, PACS radiology system and the hospital medical notes. Demographics, diagnosis on admission, co-morbidities such as DM, HTN, CCF, smoking status, cholesterol level, diseased arteries, number of revascularizations, treated and untreated disease were documented. All patients demonstrated a native coronary lesion of intermediate severity (stenosis diameter, 50 to 70%) on coronary angiography. Positive FFR was defined as ≤ 0.80. Results: 58 patients had a positive FFR study, out of which, 57(98%) underwent percutaneous revascularization, whereas, 74 patients had negative FFR studies and were managed medically.In the 7 year followup, 4 /58 patients (6.8%) had an acute coronary event in the positive FFR group while 3/74 (4.0%) had an acute coronary event in the negative FFR group and 1 patient (1.3%) required a repeat procedure.There was no significant difference between smoking status, DM, hypertension or Cholesterol status.Multivariate analysis of data is ongoing ms. Conclusions: FFR assessment is an accurate diagnostic tool for determining the prognostic significance of an intermediate coronary lesion. FFR ≤ 0.80was associated with an increased occurrence of cardiac events during long-term follow-up. FFR ≥0.80 in patients with single or multivessel coronary artery disease was associated with reduced rate of composite end point of death, nonfatal myocardial infarction, and repeat revascularization at 7 years.